URGENSI METODE KETELADANAN PADA PENDIDIKAN MASA KINI - Damanhuri, Damanhuri (LP3M STAI DARUSSALAM LAMPUNG, 2014)
Exemplary method in Islamic education is the most convincing methodthat has in fluenced to a great deal the success of character buildingof students such as moral, spiritual and social. Lack of role model amongeducatorsin practiceing Islamic values is seen as oneof the factor scontributing to a moral crisis. Its applicationin Islamic educationis not onlysupported bye ducators, butalsoby the synergy between parentsandtheen vironment. Exemplarymodels demonstrated by the educators,parentsandcommunity,consciously ornot, areattached tothemselves,eitherin their speeches, deeds, andother material and spiritual things.Educatorsmust beable toact asrole modelsfortheir students, as well asparentsfor their children. And all people can bea good examplein their life.Keyword: followed example, Islamic Education, now adays.